TEACHING IDIOMS IN ENGLISH LANGUAGE EDUCATION: A PRACTICAL GUIDE (Modern education and development, 2025)
This article explores the essential role of idioms in English language acquisition, emphasizing their importance for both comprehension and fluency. It delves into various aspects of idiom instruction, including the definition and categorization of idioms, practical teaching strategies, and the use of technology to enhance learning. The paper also addresses the challenges educators and learners face and offers solutions to overcome these obstacles. By focusing on the cultural significance and communicative value of idioms, this article promotes a comprehensive approach to idiom instruction that will improve learners' overall English language proficiency.